B cell receptor-induced growth arrest and apoptosis in WEHI-231 immature B lymphoma cells involve cyclic AMP and Epac proteins - Grandoch, Maria; López de Jesús, Maider; Oude Weernink, Paschal A.; Weber, Artur-Aron; Jakobs, Karl H.; Schmidt, Martina (Cellular signalling, 2009)
Signaling by the B cell antigen receptor (BCR) is essential for B lymphocyte homeostasis and immune function. In immature B cells, ligation of the BCR promotes growth arrest and apoptosis, and BCR-driven balancing between pro-apoptotic extracellular signal-regulated kinase 1 and 2 (ERK1/2) and anti-apoptotic phosphoinositide 3-kinase-dependent Akt seems to define the final cellular apoptotic response. Dysfunction of these late BCR signaling events can lead to the development of immunological diseases. Here we report on novel cyclic AMP-dependent mechanisms of BCR-induced growth arrest and apoptosis in the immature B lymphoma cell line WEHI-231. BCR signaling to ERK1/2 and Akt requires cyclic AMP-regulated Epac, the latter acting as a guanine nucleotide exchange factor for Rap1 and H-Ras independent of protein kinase A. Importantly, activation of endogenously expressed Epac by a specific cyclic AMP analog enhanced the induction of growth arrest (reduced DNA synthesis) and apoptosis (nuclear condensation, annexin V binding, caspase-3 cleavage and poly-ADP-ribose polymerase processing) by the BCR. Our data indicate that cyclic AMP-dependent Epac signals to ERK1/2 and Akt upon activation of Rap1 and H-Ras, and is involved in BCR-induced growth arrest and apoptosis in WEHI-231 cells.